An Occult HPV-Driven Oropharyngeal Squamous Cell Carcinoma Discovered Through a Saliva Test - Tang, Kai Dun; Vasani, Sarju; Taheri, Touraj; Walsh, Laurence J.; Hughes, Brett G. M.; Kenny, Lizbeth; Punyadeera, Chamindie (Frontiers in Oncology, 2020)
Oropharyngeal cancer (OPC) caused by human papillomavirus (HPV) is a rising global concern. Early lesions are small and are often located in difficult to access areas (such as the crypts of the tonsils or base of tongue). Unlike cervical cancer, there is no standard or routine screening program for HPV-driven OPC. HPV DNA from OPC tumours may shed directly into saliva, and this can be used as a biomarker for early diagnosis. In this study, we report the first-ever clinically occult OPC in an asymptomatic patient discovered through a saliva test. This case relied upon serial measurements of HPV-16 DNA in saliva, which fell to undetectable levels following low morbidity, curative treatment.